Life-cycle and intergenerational effects of child care reforms - Marc K. Chan; Kai Liu (Quantitative Economics, 2018)
We investigate the importance of various mechanisms by which child care policies can affect life-cycle patterns of employment and fertility among women, as well as long-run cognitive outcomes among children. A dynamic structural model of employment, fertility, and child care use is estimated using Norwegian administrative data. The estimation exploits a large-scale child care reform, which provided generous cash transfers to mothers who did not use formal child care facilities. We find that the reform generates sizable changes in employment and fertility decisions, especially among low-education women. We then use the mothers' unobserved heterogeneity in the structural model as a control function to examine the effects of mothers' behavior on long-run cognitive outcomes of children. The reform leads to lower reading scores among children, primarily as a result of mothers shifting to inferior forms of care. In counterfactual simulations, we compare the effects of an alternative child care subsidy, an expanded maternity leave program, and a tax deduction for mothers with children.
Keywords: C35; J13; J22; H31; I28; 330; Female labor supply; child care reform; fertility cognitive development of children; discrete choice dynamic programming